EFFECT OF ACCOUNTABILITY, SERVICE QUALITY, TRUST MUZZAKKI TOWARDS MUZZAKI LOYALTY - Jumriani Jumriani (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2020)
Influence of accountability, quality of service, belief Muzakki on loyalty Muzzak. This research aims to discuss the influence of accountability, quality of service, trust Muzakki against Muzzaki loyalty to the institution Muzakki Management Institute Infaq (LMI) Surabaya. The research method is using a quantitative approach. The Unit of analysis in research is to use respondents Muzzaki for 100 Muzzaki in the area of Surabaya, with the research instrument using the questionnaire in the area of Surabaya, and the method of data analysis using multiple linear regression. The results showed that the simultaneous influence was positive and significant and partiality that accounting was influential towards Muzzaki loyalty, the quality of service was influential on Muzzaki loyalty, and Muzzaki's belief had an effect on Muzzaki loyalty.